Romantic relationships, adolescence and HIV: Love as an element of vulnerability - Aguiar, Adriana de; Camargo, Brigido Vizeu (Paidéia (Ribeirão Preto), 2014)
This study investigated the relation between love and different romantic relationships with variable vulnerability to HIV, such as sexual behavior and risk perception. Sternberg’s Triangular Love Scale and a structured questionnaire were used to ask 301 high school students about: romantic relationships, sexual behavior and risk perceptions. It was identified that the adolescents underestimate their own risk of contagion when they compare themselves with other individuals and also when they consider past and future possible HIV contagion. Love does not appear to be directly associated with the self-perception of risk, however, in conjunction with dating, it is a complicating factor for protected sex and was also related to the underestimation of risk of the partner. It was observed that stable relationships and love increase the students’ vulnerability to acquire HIV, because of the association of these with trust in the partner and the justification of risky practices, such as the non-use of condoms.